Magnetic resonance imaging in the prenatal diagnosis of neural tube defects - Zugazaga Cortazar, A. (Springer Berlin Heidelberg, 2013)
OBJECTIVE: To assess the role of magnetic resonance imaging (MRI) in the prenatal diagnosis of neural tube defects (NTDs). BACKGROUND: NTDs comprise a heterogeneous group of congenital anomalies that derive from the failure of the neural tube to close. Advances in ultrasonography and MRI have considerably improved the diagnosis and treatment of NTDs both before and after birth. Ultrasonography is the first technique in the morphological study of the fetus, and it often makes it possible to detect or suspect NTDs. Fetal MRI is a complementary technique that makes it possible to clear up uncertain ultrasonographic findings and to detect associated anomalies that might go undetected at ultrasonography. The progressive incorporation of intrauterine treatments makes an accurate diagnosis of NTDs essential to ensure optimal perinatal management. The ability of fetal MRI to detect complex anomalies that affect different organs has been widely reported, and it can be undertaken whenever NTDs are suspected. CONCLUSION: We describe the normal appearance of fetal neural tube on MRI, and we discuss the most common anomalies involving the structures and the role of fetal MRI in their assessment. KEY POINTS: • To learn about the normal anatomy of the neural tube on MRI • To recognise the MR appearance of neural tube defects • To understand the value of MRI in assessing NTDs